Exploring the collaboration between formal and informal care from the professional perspective—A thematic synthesis. (9th October 2017) - Hengelaar, Aldiene Henrieke; van Hartingsveldt, Margo; Wittenberg, Yvette; van Etten‐Jamaludin, Faridi; Kwekkeboom, Rick; Satink, Ton
Abstract: In Dutch policy and at the societal level, informal caregivers are ideally seen as essential team members when creating, together with professionals, co‐ordinated support plans for the persons for whom they care. However, collaboration between professionals and informal caregivers is not always effective. This can be explained by the observation that caregivers and professionals have diverse backgrounds and frames of reference regarding providing care. This thematic synthesis sought to examine and understand how professionals experience collaboration with informal caregivers to strengthen the care triad. PubMed, Medline, PsycINFO, Embase, Cochrane/Central and CINAHL were searched systematically until May 2015, using specific key words and inclusion criteria. Twenty‐two articles were used for thematic synthesis. Seven themes revealed different reflections by professionals illustrating the complex, multi‐faceted and dynamic interface of professionals and informal care. Working in collaboration with informal caregivers requires professionals to adopt a different way of functioning. Specific attention should be paid to the informal caregiver, where the focus now is mainly on the client for whom they care. This is difficult to attain due to different restrictions experienced by professionals on policy and individual levels. Specific guidelines and training for the professionals are necessary in the light of the current policy changes in the Netherlands, where an increased emphasis is placed on informal care structures.